Adaptive modulation of microsaccades and saccade dynamics by global luminance - Kuo, Chao-Yin; Juan, Chi-Hung (Frontiers in Systems Neuroscience, 2026)
BackgroundMicrosaccades, a type of fixational eye movements occurring during visual fixation, are actively involved in the foveal vision and often linked to various attention and cognitive processes. Moreover, microsaccades are increasingly recognized as part of active adaptive mechanisms to continuously changing sensory environments. However, it remains unclear whether they also adjust to changes in luminance as part of this adaptive mechanism, and whether such luminance-regulated microsaccade responses are functionally significant.MethodsTotal forty participants were recruited in the saccade task with their eye position and pupil size measured by a video-based eye tracker. Participants were instructed to maintain fixation on a central spot and then execute a saccade to a peripheral target stimulus immediately upon detection. We systematically varied the background luminance while keeping foveal luminance constant, by which, allows isolation the effects of global luminance on microsaccade generation. We analyzed the effects of experimental condition (background luminance or stimulus contrast) on microsaccadic responses, microsaccadic suppression effects and the saccadic metrics.ResultsWe found that darker background luminance systemically increased microsaccade rates (F(2,66) = 4.490, p = 0.015) and enhanced saccadic directional accuracy (F(2,44) = 8.314, p < 0.001). Microsaccades suppressions are significant in all experimental conditions, resulting in reduced saccadic directional accuracy and slower reaction times. Notably, the presence of peri-target microsaccade altered the dynamics of saccades, leading to higher peak velocity, larger amplitude, and greater endpoint deviation.ConclusionThese findings demonstrate that microsaccade behavior changes as a function of global luminance level, suggesting its adaptive role as part of the oculomotor network. They also suggest a potential role for luminance-driven modulation of superior colliculus activity in oculomotor activities. Taken together, our results offer a new insight into visual–motor coordination under naturalistic conditions.